2018
DOI: 10.3390/md16050152
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Approach to Sustainable Marine Invertebrate Chemistry and a Scale-Up Technology for Open Marine Ecosystems

Abstract: Isolation of marine compounds from living invertebrates represents a major challenge for sustainable and environmentally friendly exploitation of marine bio-resources. To develop innovative technology to trap invertebrate compounds in the open sea, the proof of concept of a system combining external continuous circulation of water with XAD-amberlite solid-phase extraction was validated in an aquarium. In this work, we reported the elicitation of guanidine alkaloid production of Crambe crambe in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…To circumvent this problem, microbial and NP diversity can also be accessed via extraction of organisms and/or their NPs in situ. To directly gain compounds produced in the natural marine environment (which may be missed otherwise), resin capture technology can be used to capture compounds on inert sorbent supports ready to be desorbed, analysed and tested for biological activity 146 . Sustainable approaches for in situ extraction with green solvents, such as glycerol or natural deep eutectic and ionic solvents (NADES), could be used directly during field work 147 , 148 .…”
Section: Advances In Microbial Culturing Systemsmentioning
confidence: 99%
“…To circumvent this problem, microbial and NP diversity can also be accessed via extraction of organisms and/or their NPs in situ. To directly gain compounds produced in the natural marine environment (which may be missed otherwise), resin capture technology can be used to capture compounds on inert sorbent supports ready to be desorbed, analysed and tested for biological activity 146 . Sustainable approaches for in situ extraction with green solvents, such as glycerol or natural deep eutectic and ionic solvents (NADES), could be used directly during field work 147 , 148 .…”
Section: Advances In Microbial Culturing Systemsmentioning
confidence: 99%
“…Pooled EMs issued from different marine organisms constitute chemical seascapes made of thousands of distinct molecules in trace amounts (ppm, mg/L), often summarized as marine DOM. Due to their complexity, the composition of chemical seascapes has been barely explored. , Therefore, as suggested by Kelly et al, characterizing the molecular diversity of discrete source of marine EM will help not only to decipher the complexity of each chemical seascape but also to identify the ecological functions related to specific EM and possibly uncover new metabolites with biological potentials. Targeted studies performed with a few sponge species (namely, Aplysina fistularis, Agelas conifera, Aplysilla rosea, and also Crambe crambe , ) revealed that some of their specialized metabolites could be detected in the surrounding seawater. This information also suggests that sponge exometabolomes can represent unique reservoirs of structurally diverse molecules, potentially including their bioactive specialized metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers and companies working in the field of marine biotechnology can therefore solve this limitation by developing more eco-friendly technologies [ 29 ]. The use of aquaculture and alternative methods for the cultivation of marine organisms such as corals and sponges undoubtedly constitutes a sustainable production method, since the use of toxic compounds is not necessary and the raw materials can be supplied without damaging fragile marine ecosystems [ 21 , 30 ].…”
Section: Introductionmentioning
confidence: 99%